The ameliorating effect of melatonin on protamine sulfate induced bladder injury and its relationship to interstitial cystitis - ERCAN, FERİHA; ŞENER, GÖKSEL; ŞİRVANCI, SERAP (LIPPINCOTT WILLIAMS & WILKINS, 2003)
Purpose: The pineal hormone melatonin was recently shown to have free radical scavenging ability and it reduces lipid peroxidation. In this morphological study we investigated the effects of melatonin on protamine sulfate (Sigma Chemical Co., St. Louis, Missouri) induced bladder injury. Materials and Methods: Albino Wistar female rats were catheterized and intravesically infused with phosphate buffered solution (control group) or protamine sulfate (bladder injury group) dissolved in phosphate buffered solution. In the protamine sulfate plus melatonin group after protamine sulfate instillation melatonin was injected intraperitoneally. Bladder morphology was investigated by light and electron microscopy. Tissue samples were also obtained to determine bladder malondialdehyde levels. Results: In the bladder injury group ulcerated areas, an irregular glycosaminoglycan layer, increased number of mast cells, vacuole formation, dilated perinuclear cistern, formation of pleomorphic and uniform microvilli, and dilated urothelial intercellular spaces were observed. In the bladder injury plus melatonin group a relatively normal urothelial topography, glycosaminoglycan layer and decreased number of mucosal mast cells, some dilatation between intercellular areas, less uniform microvilli and in most areas regular tight junctions were observed. Conclusions: Increased malondialdehyde levels as a result of protamine sulfate induction lead us to propose that free radicals may have a critical role in this injury. The significant decrease in malondialdehyde levels in the protamine sulfate plus melatonin group was in accordance with morphological findings. Thus, melatonin appears to exert a urothelial protective activity in a bladder injury model.
Keywords: bladder; cystitis, interstitial; protamine sulfate; melatonin; rats, Wistar; EPITHELIAL PERMEABILITY BARRIER; SURFACE GLYCOSAMINOGLYCANS; ANTIOXIDANT